Phytochemical and Pharmacological Evaluation of Fruits of Sonneratia apetala (Global Journal of Medical Research, 2014)
Buch.-Ham is a mangrove tree from the family, Lythraceae. The aim of the study is to evaluate analgesic, antidirrhoeal, anthelmintic, cytotoxic activity of the fruits of S. apetala. The extract showed dose dependent analgesic activity using acetic acid induced writhing inhibition of the Swiss albino mice. The extract produced 46% and 69% writhing inhibition at the doses of 250 mg/kg and 500 mg/kg body weight respectively while the standard drug (Diclofenac Sodium) produced 82% writhing inhibition at a dose of 25 mg/kg body weight. In vivo antidiarrheal activity was substantiated by significant prolongation of latent period and decrease in total number of stools at four dose level as compared to standard loperamide. In anthelmintic test the extract showed significant and dose dependent decrease in paralysis time and death time of Haemonchus contortus, where albendazole was used as standard.
Keywords: sonneratia apetala-Buch-Ham analgesic activity; antidiarrheal activity; anthelmintic test; brine shrimp lethality bioassay